Focal spot polarization distribution under polarization smoothing - Yanghui Tang; Shenlei Zhou; Shouying Xu; Cheng Liu (High Power Laser Science and Engineering)
Polarization smoothing can effectively improve the uniformity of focal spots. In this study, we theoretically and experimentally investigated the polarization synthesis of the focal spot under a birefringent wedge (BW) and speckle under the coupling of the BW and continuous phase plate. Polarization distribution was experimentally obtained using rotating quarter-wave plate measurement under a specific wedge angle. The simulated and experimental results are consistent, demonstrating that the focal spot is in a state of coexistence of elliptical and linear polarizations. In addition, the polarization state is determined by the ratio of the amplitudes and the phase difference between the sub-beams. The simulation results showed that the proportion of linear polarization increased with the separation angle of the sub-beam. In contrast, it decreased with the incident light aperture. This research is crucial for accurately describing the polarization distribution and further understanding the laser–plasma interactions.